YBM PLN's Strategy in Supporting SDGS through ZIS Potential in Maqashid Syariah Perspective - Al Mustaqim, Dede; Makarrim, Alfiyah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2024)
Introduction: Yayasan Baitul Maal (YBM) PLN has great potential in managing Zakat, Infaq, and Sadaqah (ZIS) to support Sustainable Development Goals (SDGs) through the economic pillar. Objectives: This research aims to analyze YBM PLN's strategy in supporting SDGs through ZIS from the Maqashid Syariah perspective. Method: This research uses a qualitative method with a case study approach. Primary data was obtained through interviews with YBM PLN administrators and observations of YBM PLN programs in the economic pillar. Secondary data were obtained from YBM PLN documentation and scientific publications related to SDGs and Maqashid Syariah. Results: The results showed that YBM PLN has an effective strategy in managing ZIS to support SDGs through the economic pillar. The YBM PLN program in the economic pillar has proven to be able to empower mustahik and alleviate poverty, which is in line with the goals of SDGs and Maqashid Sharia. YBM PLN plays an important role in supporting SDGs and Maqashid Sharia through effective ZIS management. Implications: This research contributes to science by providing recommendations to improve the effectiveness of YBM PLN's strategy in supporting SDGs.